Cardiac Tamponade Following Ultrasonography-Guided Trigger Point Injection. Issue 4 (December 2014) - Jung, Jae-Wook; Kim, Seong Rok; Jeon, Sang Yoon; Bang, Si Ra; Kim, Yong Han; Lee, Sang Eun
Abstract Background: Trigger point injection [TPI] is generally considered a safe and easy procedure. Findings: We describe a case of cardiac tamponade after ultrasonography [US]-guided TPI in a thin patient. The symptoms progressively appeared directly after the injection, and the patient experienced cardiogenic shock 3 h later. Cardiac tamponade was diagnosed with difficulty when US was performed near the injection site, and then pericardiocentesis was performed immediately. Conclusions: When US-guided TPI is performed near the neck and chest, the authors suggest that the entire shaft and tip of the needle be identified to prevent any critical complications during an US-guided procedure.